Epigenetic silencing of the WNT antagonist Dickkopf 3 disrupts normal Wnt/β‐catenin signalling and apoptosis regulation in breast cancer cells. Issue 10 (24th July 2013) - Xiang, Tingxiu; Li, Lili; Yin, Xuedong; Zhong, Lan; Peng, Weiyan; Qiu, Zhu; Ren, Guosheng; Tao, Qian
Abstract Dickkopf‐related protein 3 (DKK3) is an antagonist of Wnt ligand activity. Reduced DKK3 expression has been reported in various types of cancers, but its functions and related molecular mechanisms in breast tumorigenesis remain unclear. We examined the expression and promoter methylation of DKK3 in 10 breast cancer cell lines, 96 primary breast tumours, 43 paired surgical margin tissues and 16 normal breast tissues. DKK3 was frequently silenced in breast cell lines (5/10) by promoter methylation, compared with human normal mammary epithelial cells and tissues. DKK3 methylation was detected in 78% of breast tumour samples, whereas only rarely methylated in normal breast and surgical margin tissues, suggesting tumour‐specific methylation of DKK3 in breast cancer. Ectopic expression of DKK3 suppressed cell colony formation through inducing G0/G1 cell cycle arrest and apoptosis of breast tumour cells. DKK3 also induced changes of cell morphology, and inhibited breast tumour cell migration through reversing epithelial‐mesenchymal transition (EMT) and down‐regulating stem cell markers. DKK3 inhibited canonical Wnt/β‐catenin signalling through mediating β‐catenin translocation from nucleus to cytoplasm and membrane, along with reduced active‐β‐catenin, further activating non‐canonical JNK signalling. Thus, our findings demonstrate that DKK3 could function as a tumour suppressor through inducing apoptosis and regulating Wnt signalling during breast tumorigenesis.